Climbing plants of Porto Ferreira State Park, southeastern Brazil - Vargas, Betania da Cunha [UNESP]; Caldeira Oliveira, Ana Paula [UNESP]; Udulutsch, Renata Giassi [UNESP]; Marcusso, Gabriel Mendes [UNESP]; Sabino, Gabriel Pavan [UNESP]; Alves de Melo, Pablo Hendrigo [UNESP]; Martelletti Grillo, Roberta Marotti [UNESP]; Kamimura, Vitor de Andrade [UNESP]; Assis, Marco Antonio [UNESP] (Revista Biota Neotropica, 2018)
A floristic survey of climbing plants was carried out in an ecotone area of seasonal semideciduous forest (SSF) and forested savanna (CER), in Porto Ferreira State Park (PFSP), Southeastern Brazil. We sampled the reproductive specimens every month during two periods, March 2010 to September 2011 and April and July 2015. The surveys were performed by the walking method, and the sampled individuals were classified by habit, climbing mechanism and dispersal mode. Overall, 109 species, belonging to 67 genera and 29 families, were recorded; 49 species occurred in both, 29 and 31 were exclusive to SSF and CER, respectively. Bignoniaceae and Malpighiaceae were the richest families, with 17 species, followed by Sapindaceae (12 species), Asteraceae and Apocynaceae (8 species each) and Fabaceae (6). The majority of climbers were lianas, twining and anemochoric species, corresponding to 70%, 47% and 66% of all samples, respectively. In this work, we added one new family and 14 species to the Cerrado's list of climbing plants from Sao Paulo state, and 10 species to the Brazilian seasonal semideciduous forest's list. Therefore, we contributed to the understanding of diversity of climbing plants in vegetation types poorly studied for this plant group, mainly in the Cerradao, wherein we found new records for several species.
Keywords: Cerrado; Seasonal Semideciduous Forest; ecotone; climbing plants